2021
DOI: 10.1002/jdn.10107
|View full text |Cite
|
Sign up to set email alerts
|

Placental neurotrophin levels in gestational diabetes mellitus

Abstract: Objective Neurotrophins are known to influence the development and maturation of the feto‐placental unit and affect fetal growth trajectories. This study reports the levels of nerve growth factor (NGF) and brain‐derived growth factor (BDNF) in the placenta of women with gestational diabetes mellitus (GDM). Methods A total number of 60 women with GDM and 70 women without GDM (non‐GDM) were included in the study. Placental NGF and BDNF levels were measured using commercially available ELISA kits. Results Placent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…Studies on the influence of GDM on fetal and maternal blood BDNF levels are rare, characterized by small numbers, or analyzed by either mother or fetus or placenta [28][29][30][31][32][33][34][35]. Our data are complementary to previously published results and show an inverse correlation between hyperglycemia and BDNF concentration.…”
Section: Bdnf In Gdmsupporting
confidence: 82%
See 1 more Smart Citation
“…Studies on the influence of GDM on fetal and maternal blood BDNF levels are rare, characterized by small numbers, or analyzed by either mother or fetus or placenta [28][29][30][31][32][33][34][35]. Our data are complementary to previously published results and show an inverse correlation between hyperglycemia and BDNF concentration.…”
Section: Bdnf In Gdmsupporting
confidence: 82%
“…There are no studies analyzing blood levels in women with GDM compared to healthy controls. Jadhav et al [33] found no significant differences in placental BDNF levels between n = 60 patients with GDM and n = 70 non-diabetic patients. Here, the significant difference in gestational age between both groups may have been a limiting factor.…”
Section: Maternal Bdnfmentioning
confidence: 91%
“…Although the mechanisms for increased obesity risk in GDMexposed offspring are unknown, existing studies suggest a neural basis. Serum levels of neurotrophins, including nerve growth factor and brain-derived neurotrophic factor-essential for neuronal growth, development, and differentiation-are lower in pregnant women with diabetes [16] and infants prenatally exposed to GDM [17]. Offspring exposed to GDM prenatally demonstrate brain structural alterations, such as presence of hypothalamic gliosis [18,19], lower white matter integrity in sensorimotor regions [20], lower cortical excitability [21], and mixed results on hippocampal thickness [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to effects of prenatal exposure to maternal diabetes on adiposity and metabolism, there is a growing body of work showing that prenatal exposure to maternal diabetes may affect brain development. It has been shown that levels of neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) – essential for neuronal growth, development, and differentiation – were lower in pregnant women with diabetes 8 or infants prenatally exposed to maternal diabetes 9 . Infants and youth prenatally exposed to maternal diabetes also demonstrated brain structural deficits, such as reduced hippocampal thickness 10 , reduced white matter integrity in sensorimotor regions 11 , and reduced cortical excitability 12 except for one study 13 .…”
Section: Introductionmentioning
confidence: 99%
“…While the mechanisms for increased obesity risk in GDM-exposed offspring are unknown, existing studies suggest a neural basis. Serum levels of neurotrophins including nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) – essential for neuronal growth, development, and differentiation – are lower in pregnant women with diabetes(21) and infants prenatally exposed to GDM(22). Offspring exposed to GDM prenatally demonstrated brain structural alterations, such as presence of hypothalamic gliosis, lower white matter integrity in sensorimotor regions(23), lower cortical excitability(24), and mixed results on the hippocampal thickness(25, 26).…”
Section: Introductionmentioning
confidence: 99%